2018
DOI: 10.1364/oe.26.019762
|View full text |Cite
|
Sign up to set email alerts
|

Performance analysis of space multiplexing by superposed signal in multi-dimensional VLC system

Abstract: This paper first brings a single receiver multiple-input-multiple-output (SR-MIMO) model to realize the space multiplexing in the visible light communication (VLC) system. The signals from two transmitters are super-imposed in the receiver thus to realize a specially superposed modulation. Depending on the power ratio between two transmitters, various superposed signal structures can be obtained. In order to separate the superposed signal, we design a novel detection algorithm which consists of the successive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Then, α and β are set to 1 and 4, respectively. In the earlier discussion, we have concluded that by setting α and β in the channel matrix H, the equispaced 25QAM and 64QAM can be achieved [13]. After demodulation at the receiver side, a superposed parallelogram 8QAM is achieved, with five values in unequal probability projected on the x-axis, and eight values with equal probability projected on the y-axis, as shown in figure 1.…”
Section: The Svd and The Superposed Spacementioning
confidence: 95%
See 2 more Smart Citations
“…Then, α and β are set to 1 and 4, respectively. In the earlier discussion, we have concluded that by setting α and β in the channel matrix H, the equispaced 25QAM and 64QAM can be achieved [13]. After demodulation at the receiver side, a superposed parallelogram 8QAM is achieved, with five values in unequal probability projected on the x-axis, and eight values with equal probability projected on the y-axis, as shown in figure 1.…”
Section: The Svd and The Superposed Spacementioning
confidence: 95%
“…Moreover, the computational complexity of the MIMO demultiplexing problem may increase if we do not use the pilot to save bandwidth. Many solutions have been presented, such as overlay coding (OC) [10], superposition coded modulation (SCM) [11], successive interference cancellation (SIC) [12] and the look-up table (LUT) [13,14]. In [13], Qiao proposed the use of an SIC+LUT scheme in the multiple-input-single-output (MISO) VLC system to achieve a data rate of 1.5 Gbit/s in the 1.3-m indoor line-of-sight (LOS) scenario.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…After education informatization 1.0 basically solved the problem of the digitization, education informatization 2.0 will focus on exploring the deep integration of general networking, intelligent technology and education and teaching [7][8][9][10][11]. Therefore, "Internet + education" and "artificial intelligence + education" are different manifestations of education informatization 2.0.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the studies on V2V VLC mainly focus on the line-of-sight (LOS) links that the light can directly reach the receiver from the transmitter [20][21][22]. Although V2V VLC has achieved good results in the LOS link, all the light emitted by the transmitter cannot possibly be within the field of view (FOV) of the receiver [23].…”
Section: Introductionmentioning
confidence: 99%